2022
DOI: 10.5435/jaaos-d-22-00214
|View full text |Cite
|
Sign up to set email alerts
|

Underweight Body Mass Index Is Associated With Increased In-Hospital Complications and Length of Stay After Revision Total Joint Arthroplasty

Abstract: Introduction:The purpose of this study was to assess the impact of underweight status on in-hospital postoperative outcomes and complications after revision total joint arthroplasty (rTJA) of the hip and knee. Methods: Data from the National Inpatient Sample were used to identify all patients undergoing rTJA in the United States between 2006 and 2015. Patients were divided into two groups based on a concomitant diagnosis of underweight body mass index and a control normal weight group. Propensity score analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, in orthopaedic surgery specifically, countless studies have shown the adverse effects of obesity on surgical outcomes, with a more limited number of studies investigating this in patients who are underweight. [26][27][28][29][30][31] It is therefore plausible that orthopaedic surgeons have an implicit bias against overweight and obese patients, as there may be a greater degree of concern regarding poor outcomes in this patient population.…”
Section: Attitudesmentioning
confidence: 99%
“…Furthermore, in orthopaedic surgery specifically, countless studies have shown the adverse effects of obesity on surgical outcomes, with a more limited number of studies investigating this in patients who are underweight. [26][27][28][29][30][31] It is therefore plausible that orthopaedic surgeons have an implicit bias against overweight and obese patients, as there may be a greater degree of concern regarding poor outcomes in this patient population.…”
Section: Attitudesmentioning
confidence: 99%